High degree of clonal reproduction and lack of large‐scale geographic patterning mark the introduced range of the invasive vine, kudzu (Pueraria montana var. lobata), in North America. Issue 8 (23rd August 2016) - Bentley, Kerin E.; Mauricio, Rodney
Abstract : PREMISE OF THE STUDY: Pueraria montana var. lobata, or kudzu, is an invasive species whose invasion in North America is not genetically well characterized. The clonality of kudzu introduces challenges to population genetic analyses that can bias the assessment of spatial patterns of genotypes. Assessing patterns of genetic diversity while considering clonality is necessary to understand the invasion and spread of kudzu in its invasive range. METHODS: We screened 1747 individuals from 87 populations across the invasive range with 15 microsatellite markers and a 789 bp chloroplast region. We performed detailed clonal analyses and tested levels of genetic diversity, population structure, and phylogeographic relationships. KEY RESULTS: Kudzu exhibited a clonal rate of 80%, and was more heterozygous than other long‐lived perennials. We detected only 353 distinct clonal lineages, with over 60% sharing a maternal haplotype. Populations were established with few genotypes, many consisting of only a single clone. We found no isolation by distance. Despite high genetic diversity, we found little geographic patterning. CONCLUSIONS: Kudzu is highly clonal with few genetically distinct lineages and haplotypes existing in the introduced range. Our data are consistent with a large single introduction, or a few at most. Introduced lineages are geographically randomly distributed but isolated, suggesting that genotypes rarely expand into already established populations. No route of expansion was detectable from an original introduction. The invasion of kudzu does not seem to have been dominated by a single genotype, thus standing genetic variation and phenotypic plasticity are more likely mechanisms explaining kudzu's invasion success.